State of the art of augmented reality capabilities for civil infrastructure applications - Jiaqi Xu; Derek Doyle; Fernando Moreu (Engineering Reports, 2023)
Abstract Augmented reality (AR) is a technology superimposes interactional virtual objects onto a real environment. Since the beginning of the millennium, AR technologies have rapidly grown, with significant research publications in engineering and science. However, the civil infrastructure community has minimally implemented AR technologies to date. Civil engineers face one of the challenges when understanding and using AR is the lack of a classification of AR in the context of capabilities for civil infrastructure applications. Like most engineering fields, practitioners in civil infrastructure prioritize understanding a new technology's maturity level before considering its adoption and field implementation. This article compares the capabilities of 16 AR head‐mounted devices (HMDs) available in the market since 2017, ranking them in terms of performance for civil infrastructure implementations. Finally, the authors recommend a development framework for functional AR interfaces with civil infrastructure and operations.